Correlation of community-based tourism with sustainable development to improve community welfare: a review - Putu Nuniek Hutnaleontina; I Komang Gede Bendesa; I Gusti Wayan Murjana Yasa (International Journal of Applied Sciences in Tourism and Events, 2022)
Using a literature review methodology, this research investigates the correlation of community-based tourism (CBT) with sustainable development to improve community welfare with a literature review approach. The results in this study are based on previous studies that discuss related topics to the topic being studied. The study showed a correlation between community-based tourism and sustainable development to improve community welfare. The CBT model has a positive effect on managing and empowering local communities while still paying attention to the potential of natural resources, the skills of local communities, the socioeconomic and cultural communities of local communities, and the preservation of the environment to stay sustainable. Applying the CBT model to manage tourism areas is very effective because all activities involve the community in planning, management, and development while still paying attention to local cultural aspects. Tourism policy-makers and those in control of tourist sites should be able to develop and implement a community-based tourism model in order to achieve the Sustainable Development Goals. Thus, directly and indirectly, community-based tourism changes people's perceptions by increasing community participation in tourism activities and increasing the value of people who carry out tourism activities, with implications for improving welfare.